Effects of charcoal and physical state of medium on micropropagation of black mulbery (Morus nigra L.) - Sevgin, Nevzat; Khorsheed Khalid, Aveen; Özkul, Merve (Ege Universitesi, 2023)
Objective: The purpose of this research was to investigate the effects of charcoal and physical state of culture medium on growth of Morus nigra. L. Material and Methods: For the study tree mature black mulbery (M. nigra) genotypes A5, T6 and T8 grown in vitro were used as the explant source in this study. To find out the possible effects of charcoal and culture physical state (culture medium) on culture growth used four) Liquid Nas and Read Medium (NRM) + 0.5 gl-1 activated charcoal, Liquid NRM containing no charcoal, Gelled NRM + 0.5 gl-1 activated charcoal, agar-gelled NRM containing no charcoal) medium were used in the study to find out the possible effects of the presence of charcoal and physical state of the culture medium on culture growth. Results: Medium physical state and presence of activated charcoal in the medium greatly affected mean shoot number per cultured explants. Mean shoot numbers obtained per explants varied between 1.1 and 5.8. Medium containing no charcoal produced more shoots compared to medium containing charcoal and agar - gelled medium produced more shoots compared to liquid medium. Conclusion: Agar- The gelled medium with agar gave better results for black mulbery (M. nigra) than the liquid medium. © 2023 The authors.
Aktif karbon ve kültür ortamının fiziksel halinin Urmu dutu (Morus nigra L.) nun mikroçoğaltımı üzerine etkisi
Keywords: Activated charcoal; gelled medium; in vitro; liquid medium; Morus nigra L